(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The closure of educational institutions following the rapid spread of the COVID-19 pandemic called for the adoption of online teaching and learning. For decades, education has suffered in sub-Saharan Africa due to inadequate resources and the nation’s inability to invest in continuous professional development that aims to keep practitioners abreast of the field. Most higher education institutions had not anticipated the shift to online teaching on such a massive scale and the sector was not well prepared for the challenge. This hands-on article is a reflection on the impact of the COVID-19 pandemic on History Education in higher education in Eswatini. The reflection intends to bring to light the challenges encountered and the opportunities offered for a new digital pedagogy for History Education in Eswatini as a new educational landscape emerged.